Jesus histórico e a américa-latina: desenvolvimento e contribuições em meio à Teologia Latino-Americana - Guedes, Mateus Soares (Plura, revista de estudos de religião, 2021)
This article investigates how Latin American theology sees the historical Jesus and builds his theology from it, as well as observing the implications for society. To do this, it is necessary to understand what this Historical Jesus is. The Historical Jesus is understood as the result of scientific interdisciplinary research, which is characteristic of the third phase of the research on Jesus, the third quest. Thus, it is noted that Latin American theology welcomes the results of this research on Jesus and from this builds his theology, having an important task, discussing faith and history. In this way, Latin American theologians will understand that the Historical Jesus is the basis of faith, so the starting point for a Latin American Christology must be the historical Jesus. Thus, since the historical observation of Jesus, Jesus is understood during a context of oppression and injustice, which applies his message to these contexts. Considering that the message and life of Jesus is imbued with various social, economic, political, and ideological aspects, the theology presented in Latin America must also be involved in a fight against oppression and social injustice, since the political and social context of Latin America is imbued with various types of oppression, exploitation, and injustice.